2017
DOI: 10.1002/2016wr019831
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying model structural error: Efficient Bayesian calibration of a regional groundwater flow model using surrogates and a data‐driven error model

Abstract: Groundwater model structural error is ubiquitous, due to simplification and/or misrepresentation of real aquifer systems. During model calibration, the basic hydrogeological parameters may be adjusted to compensate for structural error. This may result in biased predictions when such calibrated models are used to forecast aquifer responses to new forcing. We investigate the impact of model structural error on calibration and prediction of a real‐world groundwater flow model, using a Bayesian method with a data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 69 publications
(145 reference statements)
0
64
0
Order By: Relevance
“…However, an LSM may be overfitted by parameter optimization if the model structural errors caused from simplified or even incorrect conceptualization of the real land system are not sufficiently considered (Kennedy & O'Hagan, ). Recently, by assuming the prior distributions of structural errors, parametric uncertainty in a groundwater flow model (Xu et al, ; Xu & Valocchi, ) and a climate model (McNeall et al, ; Williamson et al, ) were investigated, but Brynjarsdóttir and O'Hagan () demonstrated that only with realistic priors on the model structural errors could they uncover the true parameter values. Therefore, acceptable prior distributions of model structure errors are necessary to reasonably calibrate the parameters.…”
Section: Introductionmentioning
confidence: 99%
“…However, an LSM may be overfitted by parameter optimization if the model structural errors caused from simplified or even incorrect conceptualization of the real land system are not sufficiently considered (Kennedy & O'Hagan, ). Recently, by assuming the prior distributions of structural errors, parametric uncertainty in a groundwater flow model (Xu et al, ; Xu & Valocchi, ) and a climate model (McNeall et al, ; Williamson et al, ) were investigated, but Brynjarsdóttir and O'Hagan () demonstrated that only with realistic priors on the model structural errors could they uncover the true parameter values. Therefore, acceptable prior distributions of model structure errors are necessary to reasonably calibrate the parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Using multiple summary metrics that measure relevant parts of system behavior, we can gain information about how and where the model may be improved (Sadegh et al, 2015;Vrugt & Sadegh, 2013). In future works, we can simultaneously consider the surrogate and the model structural errors by combining the approach proposed in this work with methods that address model structural inadequacy (e.g., Duan et al, 2007;Madadgar & Moradkhani, 2014;Xu et al, 2017;Xu & Valocchi, 2015;Ye et al, 2010;Zeng et al, 2016;Zeng et al, 2018;Zhang et al, 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…While it is possible in principle to further modify the MCMC scheme used to incorporate such constraints, our approach offers a simple and direct way of controlling the number of fine model runs used. Xu et al (2017), Zhang et al (2018), and Lødøen and Tjelmeland (2010) apply the KOH method to account for the approximation errors, and these are incorporated into an adaptive multifidelity MCMC sampler (see, e.g., Peherstorfer et al, 2018), the differential evolution adaptive metropolis (Vrugt et al, 2009;Laloy & Vrugt, 2012) sampler, and the Metropolis-Hastings algorithm (see, e.g., Chib & Greenberg, 1995), respectively. Again, these require more sophisticated understanding and control of the MCMC scheme used and 10.1029/2018WR024240 involve infinte-dimensional stochastic processes following the approach of KOH.…”
Section: Premarginalizationmentioning
confidence: 99%